Nudging for eco-friendly online shopping – Attraction effect curbs price sensitivity. (June 2022) - Guath, Mona; Stikvoort, Britt; Juslin, Peter
Abstract: The current study investigates the efficiency of nudging people to purchase more eco-friendly electronic devices in an emulated online milieu. To this end, participants were presented with three different products (smart phones, monitors and portable speakers) with two different nudges (attraction and default) and a control condition. Results from two experiments show that, while there was already a strong preference to make eco-friendly choices in control conditions, when eco-friendly choices were costlier, there was a clear positive effect of an attraction nudge on participants' eco-friendly preferences. In other words, when product prices were generally high, or when there are large price differences between options, the attraction nudge resulted in a higher probability of eco-friendly choices compared to when no attraction effect is used. The default nudge was less efficient, sometimes producing a negative effect, while its effect was mediated by whether participants endorsed a strong bio-centric worldview, in which case the default nudge promoted more eco-friendly choices. The results are discussed in relation to potential challenges pertaining to deceit and perceived paternalistic intentions with use of nudges. Highlights: The study focuses on how to increase pro-environmental purchases online. Subjects hypothetically purchased e-devices in different choice architectures. Two experiments show that nudging can increase eco-friendly decisions online. Nudging is a potential policy instrument for sustainable online consumption.